Nano Influencers And Social Factors As Drivers Of Hedonic Consumption Among Generation Z In Indonesia's Social Commerce - Kembau, Agung Stefanus; Pangaribuan, Christian Haposan; Hong, Kristy (Journal of Entrepreneurship & Business, 2025)
Purpose: This study seeks to shed light on the often-overlooked role of nano influencers in shaping hedonic consumption among Generation Z (Gen-Z) in Indonesia’s rapidly evolving social commerce landscape. While much attention has been given to macro influencers, our research suggests that smaller, more trusted voices may hold the key to authentic consumer engagement. Method: A cross-sectional survey of 200 Gen-Z consumers was conducted, utilizing Structural Equation Modeling (SEM) via Smart PLS to analyze the influence of nano influencers, reference groups, and communities on hedonic consumption. The research framework focuses on the social dynamics of peer validation over family influence. Result: The findings indicate that nano influencers significantly enhance the influence of peer groups on Gen-Z’s hedonic consumption, while family influence appears less relevant. This result points to a shift in consumer behavior, where peer-driven validation is dominant. Marketers are encouraged to reconsider their strategies, placing greater emphasis on nano influencers for more genuine connections in the social commerce era.